2015
DOI: 10.1038/nplants.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation by translational inhibition is determined by Dicer partnering proteins

Abstract: MicroRNAs (miRNAs) are small regulatory RNAs produced by Dicer proteins that regulate gene expression in development and adaptive responses to the environment(1-4). In animals, the degree of base pairing between a miRNA and its target messenger RNA seems to determine whether the regulation occurs through cleavage or translation inhibition(1). In contrast, the selection of regulatory mechanisms is independent of the degree of mismatch between a plant miRNA and its target transcript(5). However, the components a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 29 publications
4
102
0
2
Order By: Relevance
“…PCA plots with r-log normalized counts data and differential expression analysis (Wald test, multiple testing adjustment of P values with Benjamini-Hochberg procedure) were performed in the Bioconductor environment (Gentleman et al, 2004) using DESeq2 version 1.4.5 (Love et al, 2014) workflow. The list of validated and predicted miRNA and tasiRNAs targets used for data analyses (Supplemental Table S10) was updated from Reis et al (2015).…”
Section: Bioinformatic Analysis Of Mrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…PCA plots with r-log normalized counts data and differential expression analysis (Wald test, multiple testing adjustment of P values with Benjamini-Hochberg procedure) were performed in the Bioconductor environment (Gentleman et al, 2004) using DESeq2 version 1.4.5 (Love et al, 2014) workflow. The list of validated and predicted miRNA and tasiRNAs targets used for data analyses (Supplemental Table S10) was updated from Reis et al (2015).…”
Section: Bioinformatic Analysis Of Mrnasmentioning
confidence: 99%
“…In animals, there is good evidence for the existence of mechanisms of repression both at initiation and postinitiation levels (Olsen and Ambros, 1999;Seggerson et al, 2002;Pillai et al, 2005;Maroney et al, 2006;Nottrott et al, 2006;Petersen et al, 2006;Fukaya et al, 2014), but the precise molecular nature of these mechanisms has not been clearly defined. In plants, mechanisms of translational repression by miRNAs remain nearly completely unknown, and although genetic screens have identified some genes required for the process (Brodersen et al, 2008;Yang et al, 2012a;Li et al, 2013;Reis et al, 2015), none of them provides clear insight into how AGO1 recruitment to an mRNA may bring about its translational repression. mRNA degradation is another common outcome of AGO recruitment.…”
mentioning
confidence: 99%
“…Following duplex strand separation, DRB1 directs the selective loading of miRNA guide strands onto AGO1 to form miRNA-loaded RISC (miRISC) [9]. In plants, miRISC can repress the expression of highly complementary target transcripts via directing either a transcript cleavage or translation inhibition, and the selection of either mechanism is determined by DCL1 partnering proteins, DRB1 (cleavage) and DRB2 (translation inhibition) [10] (Figure 1). …”
Section: Small Noncoding Rnas In Plantsmentioning
confidence: 98%
“…It has been shown that DRBs might have similar functions in plant miRNA loading to AGOs (Eamens et al, 2009). It is also been reported that the outcome of miRNA targeting i.e., either target cleavage or translational inhibition is governed by dsRNA binding partners of DCL1 (Reis et al, 2015a). HYL1 mediates target cleavage while DRB2 mediates translational inhibition.…”
Section: Loading Of Mirna Into Ago and Silencingmentioning
confidence: 99%